2016
DOI: 10.1159/000450949
|View full text |Cite
|
Sign up to set email alerts
|

Disease Manifestation and Inflammatory Activity as Modulators of Th17/Treg Balance and RORC/FoxP3 Methylation in Systemic Sclerosis

Abstract: Background: There is much evidence that T cells are strongly involved in the pathogenesis of localized and systemic forms of scleroderma (SSc). A dysbalance between FoxP3+ regulatory CD4+ T cells (Tregs) and inflammatory T-helper (Th) 17 cells has been suggested. Methods: The study aimed (1) to investigate the phenotypical and functional characteristics of Th17 and Tregs in SSc patients depending on disease manifestation (limited vs. diffuse cutaneous SSc, dcSSc) and activity, and (2) the transcriptional level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 56 publications
0
26
1
2
Order By: Relevance
“…Treating SSc CD4+ T cells with a DNMT inhibitor not only reduced DNA methylation levels, but also increased FOXP3 expression and number of Tregs. These results contradicted the recent study reported by Almanzar et al, where they showed increased FOXP3 expression and the number of Tregs in SSc patients, with no significant change in DNA methylation in FOXP3 regulatory regions in peripheral blood mononuclear cells (PBMCs) [84]. They reported that Th17-specific transcription factors, RORC1 and 2, were hypermethylated in PBMCs.…”
Section: Epigenetic Impact In Ssc Pathogenesiscontrasting
confidence: 74%
“…Treating SSc CD4+ T cells with a DNMT inhibitor not only reduced DNA methylation levels, but also increased FOXP3 expression and number of Tregs. These results contradicted the recent study reported by Almanzar et al, where they showed increased FOXP3 expression and the number of Tregs in SSc patients, with no significant change in DNA methylation in FOXP3 regulatory regions in peripheral blood mononuclear cells (PBMCs) [84]. They reported that Th17-specific transcription factors, RORC1 and 2, were hypermethylated in PBMCs.…”
Section: Epigenetic Impact In Ssc Pathogenesiscontrasting
confidence: 74%
“…Th17 alongside with Th22 have pulmonary and cutaneous homing [23]. Larger Ssc group flow cytometry studies (135 Ssc patients) confirmed these findings [24], but also described in late Ssc patients an increase in Th2 cells in addition to Th17. As for circulating T reg cells there were no differences from healthy controls.…”
Section: Flow Cytometry Findings Regarding Th17 In Ssc Patientsmentioning
confidence: 65%
“…For example, in the presence of IL-6, Tregs is converted into Th17-secreting IL-17 cells, which further releases pro-inflammatory and fibrosis-increasing mediators. This passage of Tregs in Th17 under the influence of optimal environmental conditions may explain the reduction of Tregs lymphocytes observed in systemic sclerosis [28][29][30].…”
Section: Il-6mentioning
confidence: 93%
“…Dla przykładu, w obecności IL-6 dochodzi do konwersji Tregs w komórki Th17 -wydzielające IL-17, co powoduje dalsze uwalnianie prozapalnych oraz nasilających włóknienie mediatorów. To przejście Tregs w Th17 pod wpływem optymalnych warunków środowiska może tłumaczyć obserwowaną w twardzinie układowej redukcję limfocytów Tregs [28,29,30].…”
Section: Twardziny Układowejunclassified